Gottfried Benn y José Ángel Valente. Fragmentos traducidos de «Das Späte Ich» en el poema «XVII (el yo tardío) de Treinta y siete fragmentos (TEST Ticontre. Theory Text Translation, 2020)
For José Ángel the translation represents the way to articulate his poetic through another´s text. The fragment is also the mode of writing throughout his career. The fragment «XVII (The late Self)», integrated in Thirty Seven Fragments (1971), is a hybrid and bilingual text elaborated from the translation of fragments oft he poem «Das späte Ich», by German Gottfried Benn. First we will trace the stylistic and thematic features of Valente´s book in order to highlight certain common elements to the Poetic Expresionist movement, of wich Benn is a clear exponent. Then we will analyse the fragment «XVII (The late Self)», in the light of the German poem «Das späte Ich», which was used by Valente for his text. The ommited parts oft he original German willl help us to observe the thematic and aesthetic aspects that underlie this bilingual composition.